Transpedicular decancellation osteotomy in the treatment of peridural fibrosis - (:unkn) unknown (SPRINGER, 2001)
From 1992 to 1997 a series of 12 multiply operated (averaging 2.5 previous operations) patients with recurrent peridural fibrosis and postlaminectomy kyphosis underwent surgery at our clinic. The surgery was designed to restore the physiological lordosis and relax tethered cord and epidural veins by transpedicular decancellation osteotomy at a vertebra other than the vertebra with peridural fibrosis. This paper presents the long-term functional outcome of these 12 patients. Clinical assessments were conducted pre-operatively and at 3-month intervals postoperatively and included X-ray assessment and evaluation of the patients' functional status by Oswestry Disability Index (ODI) and of pain by visual analogue scale (pain VAS). All symptoms and the pain due to peridural fibrosis disappeared in the early postoperative period. Patients had lower disability and pain scores at their early and long-term follow-ups (follow-up period 24-74 months, mean 36.3 months). For patients with failed medical therapy for peridural fibrosis accompanied by lumbar kyphosis or hypolordosis, transpedicular decancellation osteotomy should be the surgical treatment of choice.
Keywords: peridural fibrosis; lumbar kyphosis; transpedicular decancellation osteotomy; PAIN